Comparing ceramic Fischer-Koch-S and gyroid TPMS scaffolds for potential in bone tissue engineering - Baumer, Vail; Isaacson, Nelson; Kanakamedala, Shashank; McGee, Duncan; Kaze, Isabella; Prawel, David (Frontiers in Bioengineering and Biotechnology, 2024)
Triply Periodic Minimal Surfaces (TPMS), such as Gyroid, are widely accepted for bone tissue engineering due to their interconnected porous structures with tunable properties that enable high surface area to volume ratios, energy absorption, and relative strength. Among these topologies, the Fischer-Koch-S (FKS) has also been suggested for compact bone scaffolds, but few studies have investigated these structures beyond computer simulations. FKS scaffolds have been fabricated in metal and polymer, but to date none have been fabricated in a ceramic used in bone tissue engineering (BTE) scaffolds. This study is the first to fabricate ceramic FKS scaffolds and compare them with the more common Gyroid topology. Results showed that FKS scaffolds were 32% stronger, absorbed 49% more energy, and had only 11% lower permeability than Gyroid scaffolds when manufactured at high porosity (70%). Both FKS and Gyroid scaffolds displayed strength and permeability in the low range of trabecular long bones with high reliability (Weibull failure probability) in the normal direction. Fracture modes were further investigated to explicate the quasi-brittle failure exhibited by both scaffold topologies, exploring stress-strain relationships along with scanning electron microscopy for failure analysis. Considering the physical aspects of successful bone tissue engineering scaffolds, FKS scaffolds appear to be more promising for further study as bone regeneration scaffolds than Gyroid due to their higher compressive strength and reliability, at only a small penalty to permeability. In the context of BTE, FKS scaffolds may be better suited than Gyroids to applications where denser bone and strength is prioritized over permeability, as suggested by earlier simulation studies.